MULTICULTURALISMO E GENERALIZAÇÃO: FOME ZERO - Ferreira, Dina Maria Martins (Intercâmbio, 2010)
This article deals with the displacement of the subjects in the Zero Hunger. I have chosen a route organizing through differences that construct the subjects: those that are constituted in social class pluriculturalism; and mass subjects, which become silent through the generalization.